The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1037/0735-7028.26.4.407
|View full text |Cite
|
Sign up to set email alerts
|

Training and supervision practices in clinical, counseling, and school psychology programs.

Abstract: This study surveyed the training directors of counseling, clinical, and school psychology programs accredited by the American Psychological Association on training and supervisory practices and perceptions of various modalities of supervision. Response rates were 74%, 56%, and 45%, respectively. Clinical and counseling psychology training directors reported that videotape review was the most used modality of supervision; school psychology training directors reported that self-report only was the most frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…Supervision is a neglected area of research in all of school psychology training and practice (Crespi & Dube, 2005;Harvey & Struzziero, 2008;Romans, Boswell, Carlozzi, & Ferguson, 1995;Welsh, Stanley, & Wilmoth, 2003). Extant literature on consultation supervision is mostly descriptive or theoretical, and much of what is written borrows from what is known about supervision from other psychology specialties such as Clinical and Counseling Psychology and Psychotherapy.…”
Section: Hypothesized Importance Of Consultation Supervisionmentioning
confidence: 98%
“…Supervision is a neglected area of research in all of school psychology training and practice (Crespi & Dube, 2005;Harvey & Struzziero, 2008;Romans, Boswell, Carlozzi, & Ferguson, 1995;Welsh, Stanley, & Wilmoth, 2003). Extant literature on consultation supervision is mostly descriptive or theoretical, and much of what is written borrows from what is known about supervision from other psychology specialties such as Clinical and Counseling Psychology and Psychotherapy.…”
Section: Hypothesized Importance Of Consultation Supervisionmentioning
confidence: 98%
“…teaching" (p. 83), is used in various higher professional education and training courses to improve the communication skills of a broad group of "interpersonal professionals" (Hargie et al 1983), including teachers, psychologists, social workers, doctors and nurses, for whom effective communication plays a vital role in their work (see Baker et al 1990;Beckman and Frankel 1994;Gask 1992;Hill and Lent 2006;Hulsman et al 1999;Huhra et al 2008;Perlberg 1983;Quigley and Nyquist 1992;Romans et al 1995;Schoonover et al 1983;Sherin 2004;Silverman et al 2005).…”
mentioning
confidence: 97%
“…Examples of techniques include case consultation, cofacilitation of activities, live observation, audio/videotaping, role playing, supervisor modeling/supervisee rehearsal, and written information (e.g., process notes, progress notes, and transcription). Even though a number of techniques may be relevant to apply, supervisors do not always select a wide range of strategies or implement the ones they view as most effective (Romans et al, 1995). For a further description of supervisory techniques, including advantages and disadvantages, the reader is referred to Harvey and Struzziero (2008).…”
Section: Techniquesmentioning
confidence: 97%
“…For example, descriptive studies have demonstrated (a) limited availability and perceived insufficiency of clinical supervision for practicing school psychologists (Chafouleas, Clonan, & Vanauken, 2002;Curtis, Castillo, & Gelley, 2012;Fischetti & Crespi, 1999); (b) a lack of supervision techniques other than case consultation (i.e., talking about cases) predominately applied by supervisors (Cochrane, Salyers, & Ding, 2010;Romans, Boswell, Carlozzi, & Ferguson, 1995;Ward, 2001); and (c) supervisors (both field and university) not having completed supervision coursework, ongoing professional development on supervision, or formal metasupervision (i.e., supervision of supervision; Cochrane et al, 2010;Ward, 2001). A number of factors may account for the gap between the purported value of supervision and what is actually practiced, including complexity in defining and researching supervision (Knoff, 1986;McIntosh & Phelps, 2000).…”
mentioning
confidence: 98%